Early to Middle Holocene transition in the Pastos Chicos record, dry Puna of Argentina - Tchilingurian, Pablo (2014)
This paper presents a multi-proxy record and its paleoenvironmental interpretation from Pastos Chicos (23 400 2900 S; 66 250 3200 W; 3781 m asl), Susques, Jujuy province, Argentina. The analysis includes a study of fluvial sediments and geomorphology, and the contained diatoms and pollen record at centenary resolution. Two main environmental phases characterize the w9000e4200 BP interval. The first phase was a humid period between w9000 and 7300 BP (circa 10,000e8100 cal. BP) which showed organic soils formation in a floodplain broadly vegetated by grasses with a high and stable water table level. The second phase developed between 7300 and 6000 BP (w8100e6800 cal. BP) and showed a moderately drier environment interrupted by punctuated humid events such as those around 7000 and 6300 BP. This environment could be interpreted as a permanently existing meandering river with a floodplain with shallow oxbow lakes, bordered by a diverse shrub steppe. After 6000 BP, the fluvial system turned into a braided river situated in a sandy floodplain with dunes and ephemeral ponds. At the end of the sequence (i.e. post w4200 BP), salt crusts developed and the river lowered its base level by 8 m. These results seem to show that the Pastos Chicos river basin evolved from low energy and more humid conditions established during the Early and the first part of the Middle Holocene, to drier ones in a system with more energy during some events of the second part of the latter period. The start of this aridization process at w6000 BP in the basin, seems to be substantially later than other observations in local records of the Andean area. This could be due to physiographic control of the moisture by the catchment area (w1000 km2) that generates a catchment-averaged regional scale signal of smaller amplitude, which is delayed for individual tributaries. These studies, with other ongoing analysis, will improve the accuracy of the models of resource structure in the area in several spaceetime scales and, consequently, advance knowledge concerning the organizational pattern of human societies in the past.